Non-Lethal Sequential Individual Monitoring of Viremia in Relation to DNA Vaccination in Fish–Example Using a Salmon Alphavirus DNA Vaccine in Atlantic Salmon Salmo salar - Collins, Catherine (Vaccines (Basel), 2021)
Traditionally, commercial testing for vaccine efficacy has relied on the mass infection of vaccinated and unvaccinated animals and the comparison of mortality prevalence and incidence. For some infection models where disease does not cause mortality this approach to testing vaccine efficacy is not useful. Additionally, in fish experimental studies on vaccine efficacy and immune response the norm is that several individuals are lethally sampled at sequential timepoints, and results are extrapolated to represent the kinetics of immune and disease parameters of an individual fish over the entire experimental infection period. In the present study we developed a new approach to vaccine testing for viremic viruses in fish by following the same individuals over the course of a DNA vaccination and experimental infection through repeated blood collection and analyses. Injectable DNA vaccines are particularly efficient against viral disease in fish. To date, two DNA vaccines have been authorised for use in fish farming, one in Canada against Infectious Haemorrhagic Necrotic virus and more recently one in Europe against Salmon Pancreatic Disease virus (SPDv) subtype 3. In the current study we engineered and used an experimental DNA vaccine against SPDv subtype 1. We measured viremia using a reporter cell line system and demonstrated that the viremia phase was completely extinguished following DNA vaccination. Differences in viremia infection kinetics between fish in the placebo group could be related to subsequent antibody levels in the individual fish, with higher antibody levels at terminal sampling in fish showing earlier viremia peaks. The results indicate that sequential non-lethal sampling can highlight associations between infection traits and immune responses measured at asynchronous timepoints and, can provide biological explanations for variation in data. Similar to results observed for the SPDv subtype 3 DNA vaccine, the SPDv subtype 1 DNA vaccine also induced an interferon type 1 response after vaccination and provided high protection against SPDv under laboratory conditions when fish were challenged at 7 weeks post-vaccination.